The Study on Thermal Expansion of Ceramic Composites with Addition of ZrW[2]O]8]; IOP Conference Series: Materials Science and Engineering; Vol. 116 : Advanced Materials and New Technologies in Modern Materials Science - Dedova E. S. Elena Sergeevna; Shadrin V. S.; Petrushina M. Y.; Kulkov S. N. Sergey Nikolaevich (2016, 2016)
Title screen